Host genotype-driven shifts in the Medicago seed microbiome reveal domestication-linked diversity loss in lucerne (Medicago sativa) - Herath Dissanayakalage, Shenali Subodha; Kaur, Jatinder; Mann, Ross C.; Sawbridge, Timothy I. (Frontiers in Microbiology, 2025)
Seed microbiomes represent a critical yet underexplored dimension of plant-associated microbial communities, with potential to enhance crop resilience and sustainability. While plant microbiomes have gained prominence, the diversity and composition of seed-associated bacteria—especially across wild and domesticated lineages—remain poorly characterised. Here, we profiled the bacterial seed microbiome of lucerne (Medicago sativa L.) and its crop wild relatives using an integrative approach combining amplicon sequencing, culture-based recovery, and whole-genome analysis of representative isolates. Amplicon profiling revealed a conserved core microbiome across all accessions, alongside host-genotype-specific patterns and markedly higher bacterial diversity in wild relatives. Culture-based methods recovered over half of the abundant amplicon sequence variants (ASVs), validating the representativeness of the isolate library. The whole genome sequencing of selected isolates uncovered substantial intra-species variation, including genomically distinct strains within the same species. Core taxa such as Pantoea, Paenibacillus, and Pseudomonas were consistently recovered, while several genera enriched in wild relatives—Massilia, Duganella, Sphingomonas—were absent or rare in domesticated lines. Comparative microbiome analysis revealed that domestication has reduced both taxonomic richness and microbial variability in the lucerne seed microbiome. The dominance of conserved taxa alongside the exclusion of wild-enriched groups suggests that breeding history influences microbial assembly and may constrain microbiome function. The consistent presence of core taxa across accessions is consistent with the possibility that, vertical transmission, together with host genotype, contributes to seed microbiome structure. By linking plant genotype with seed microbiome composition and culturability, this study provides a high-resolution view of seed microbial assembly shaped by evolutionary history. The resulting culture-based microbial resource, supported by genome-level characterisation of representative taxa, offers a robust foundation for microbiome-informed strategies in lucerne breeding and pasture improvement.